Slot dipole antenna with single- and dual-band tuning characteristic - Idris, Izni Husna (Institution of Engineering and Technology, 2014)
A slot dipole antenna with a reconfigurable operating frequency is presented. The antenna comprises two pairs of slot arms. Each arm incorporates a number of varactor diodes. The antenna is capable of operating in single-band or dual-band mode. In each case, the location of these bands can be altered by varying the voltage applied to the varactor diodes. The antenna can be tuned over a wide frequency range, namely 1.5-4.5 GHz (i.e. a ratio of 3:1). The antenna is potentially useful for cognitive radio application, particularly in a small base station or access point terminal.